Implementing Various Strategies in Teaching English through Literature in Islamic Boarding School - Untung Pararean Adjie Saputra; Wirda Farfaza Nabila Rusafi Rusafi; Wahyu Indah Mala Rohmana (English Education Postgraduate Program, Universitas Negeri Manado, 2024)
The study